INTEGRATION OF DIGITAL SUPPLY CHAIN CAPABILITIES FOR SUSTAINABLE SUPPLY CHAIN PERFORMANCE: A LITERATURE REVIEW - Sutopo Sutopo; Sudianto Sudianto; Abdul Hamid (Journal of Information Systems Management and Digital Business, 2026)
The objective of this study is to comprehensively analyze how the integration of digital supply chain capabilities including demand planning, sustainable procurement, inventory management, and supplier relationships contributes to enhancing sustainable supply chain performance. The research method employed is a qualitative approach using a literature review. The analysis followed a systematic procedure involving identification, selection, and critical evaluation through Thematic Analysis of reputable journal articles, proceedings, and scientific reports published between 2015 and 2025. The results indicate that digital capabilities improve planning accuracy through predictive analytics, strengthen transparency and traceability in procurement, optimize real-time inventory, and enhance supplier collaboration via technology-based information exchange. The integration of these four dimensions significantly improves operational efficiency, supply chain resilience, and value creation across economic, social, and environmental dimensions in line with Triple Bottom Line principles.